1988
DOI: 10.1021/j100329a022
|View full text |Cite
|
Sign up to set email alerts
|

Xenon-129 NMR of xenon adsorbed in Y zeolites at 144 K

Abstract: 129Xe NMR spectra of xenon adsorbed in Na-Y, K-Y, Mg-Y, Ca-Y, and B-Y zeolites have been measured as a function of the xenon loading at 144 and 293 K. At low xenon loadings, the 129Xe chemical shift shows two types of dependence on the xenon density in the supercage: linearly increasing and paraboliclike with a minimum. At 144 K, all the zeolites except Ca-Y have a linear dependence, whereas at 293 K, both Ca-Y and Mg-Y show a paraboliclike curvature. These dependences can be explained in terms of rapid exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 0 publications
6
52
1
Order By: Relevance
“…[381] For zeolites exchanged with divalent cations, the 129Xe NMR shift of adsorbed xenon atoms shows a parabola-like dependence on the loading. Assuming an exchange rate between xenon atoms in the gas phase and strongly adsorbed xenon atoms much faster than the 129Xe NMR relaxation rate and using an approach similar to that for the Langmuir isotherm, Cheung et al [390] found the following dependence of the chemical shift 6(T,p): ( 4.49) where 6 8 and ~g (T) are the chemical shift of xenon atoms in the adsorbed phase and the temperature-dependent chemical shift gradient in the gaseous phase, At low levels of divalent cations « 55% exchange) there is a linear relationship between the chemical shifts and the coverage. In these samples the divalent cations are located in the sodalite cages and, therefore, are not accessible for xenon atoms.…”
Section: Xe Nmr Investigations Of the Zeolitic Pore Architecturementioning
confidence: 99%
“…[381] For zeolites exchanged with divalent cations, the 129Xe NMR shift of adsorbed xenon atoms shows a parabola-like dependence on the loading. Assuming an exchange rate between xenon atoms in the gas phase and strongly adsorbed xenon atoms much faster than the 129Xe NMR relaxation rate and using an approach similar to that for the Langmuir isotherm, Cheung et al [390] found the following dependence of the chemical shift 6(T,p): ( 4.49) where 6 8 and ~g (T) are the chemical shift of xenon atoms in the adsorbed phase and the temperature-dependent chemical shift gradient in the gaseous phase, At low levels of divalent cations « 55% exchange) there is a linear relationship between the chemical shifts and the coverage. In these samples the divalent cations are located in the sodalite cages and, therefore, are not accessible for xenon atoms.…”
Section: Xe Nmr Investigations Of the Zeolitic Pore Architecturementioning
confidence: 99%
“…Cheung et al [7] also used the fast site exchange model and expressed the chemical shift of xenon adsorbed in Y zeolites at temperature T and concentration p as:…”
Section: Na+n 'mentioning
confidence: 99%
“…The probability of finding a xenon atom at the surface is given by, rp.easured for xenon in NaY zeolite at 144 K. [ 176] In view of the much smaller heat of adsorption of xenon on the polymer as compared to a zeolite, this large value for 8 5 is surprising. However for NaY 8 5 increases from 58 ppm at room temperature, to 86 ppm at 144 K, the only low temperature measured, so it may increase further at even lower \ temperatures.…”
Section: Theoretical Discussionmentioning
confidence: 99%